Eye tracking sentences in language education - Marcus Maia (Diacrítica, 2022)
The present study reports and discusses the use of eye tracking qualitative data (dynamic gaze plots and heatmaps) in reading workshops in a middle school and in Generative Syntax and Sentence Processing courses at the undergraduate and graduate level. Both endeavors take the sentential level as the proper object to be metacognitively explored in language education in order to develop innate science forming capacity and knowledge of language. In both projects non-discrepant qualitative eye tracking data collected and quantitatively analyzed in psycholinguistic studies carried out in Lapex (Experimental Psycholinguistics Laboratory of the Federal University of Rio de Janeiro) were displayed to students as a point of departure, triggering discussions. Active, problem-solving based methodologies were employed with the objective of stimulating student participation. The article also discusses the importance of developing full literacy, epistemic vigilance and intellectual self-defense in an infodemic world.